Rat intra-hippocampal NMDA infusion induces cell-specific damage and changes in expression of NMDA and GABAA receptor subunits - Rambousek, Lukas; Kleteckova, Lenka; Kubesova, Anna; Jirak, Daniel; Vales, Karel; Fritschy, Jean-Marc (Neuropharmacology, 2016)
Excessive stimulation of NMDA receptors with glutamate or other potent agonists such as NMDA leads to excitotoxicity and neural injury. In this study, we aimed to provide insight into an animal model of brain excitotoxic damage; single unilateral infusion of NMDA at mild dose into the hippocampal formation. NMDA infusion induced chronic, focal neurodegeneration in the proximity of the injection site. The lesion was accompanied by severe and progressive neuroinflammation and affected preferentially principal neurons while sparing GABAergic interneurons. Furthermore, the unilateral lesion did not cause significant impairment of spatial learning abilities. Finally, GluN1 and GluN2B subunits of NMDA receptor were significantly upregulated up to 3 days after the NMDA infusion, while GABAA α5 subunit was downregulated at 30 days after the lesion. Taken together, a single infusion of NMDA into the hippocampal formation represents an animal model of excitotoxicity-induced chronic neurodegeneration of principal neurons accompanied by severe neuroinflammation and subunit specific changes in NMDA and GABAA receptors.
Keywords: Receptors, GABA-A; bludiště - učení; degenerace nervu; Neuroimmunomodulation; funkční lateralita; neurodegenerativní nemoci; Disease Models, Animal; neurony; zvířata; potkani Long-Evans; Hippocampus; Animals; Neurons; N-Methylaspartate; modely nemocí na zvířatech; Nerve Degeneration; Rats, Long-Evans; receptory GABA-A; Neurodegenerative Diseases; neuroimunomodulace; Receptors, N-Methyl-D-Aspartate; Male; hipokampus; mužské pohlaví; receptory N-methyl-D-aspartátu; N-methylaspartát; Maze Learning; Functional Laterality